Good teaching: the top ten requirements - F. Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (Universiti Teknologi MARA, Sarawak, 2004)
This article outlines the top ten qualities of good teaching, emphasizing passion, communication, flexibility, creativity, leadership, and care for students. It highlights that effective teaching involves understanding students, adapting to their needs, maintaining professionalism, and creating an engaging, supportive learning environment. The piece also stresses the importance of humor, teamwork, continual improvement, and enjoying the teaching process itself.